Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - 7.5 - Fractional Equations and Problem Solving - Problem Set 7.5: 27

Answer

$n = 37$

Work Step by Step

1. Multiply by $49-n$ on both sides of the equation to remove the fractions: $\frac{n}{49-n} = 3 + \frac{1}{49-n}$ $n = 3(49-n) + \frac{1(49-n)}{49-n}$ $n = 3(49-n) + \frac{49-n}{49-n}$ 2. Simplify the fraction $n = 147 - 3n + 1$ $-147 + n + 3n - 1 = 0$ $-148 + 4n = 0$ $4(-37 + n) = 0$ (Factor $4$ out) $-37 + n = 0$ $n = 37$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.